Interest rate changes and stock returns in Spain: A wavelet analysis - Pablo Moya-Martínez; Roman Ferrer-Lape\~na; Francisco Escribano-Sotos (BRQ Business Research Quarterly, 2015)
This paper investigates the relationship between changes in interest rates and the Spanish stock market at the industry level over the period from January 1993 to December 2012 using a wavelet-based approach. The empirical results indicate that Spanish industries exhibit, in general, a significant interest rate sensitivity, although the degree of interest rate exposure differs considerably across industries and depending on the time horizon under consideration. In particular, regulated industries such as Utilities, highly indebted industries such as Real Estate, Utilities or Technology and Telecommunications, and the Banking industry emerge as the most vulnerable to interest rates. Further, the link between movements in interest rates and industry equity returns is stronger at the coarsest scales. This finding is consistent with the idea that investors with long-term horizons are more likely to follow macroeconomic fundamentals, such as interest rates, in their investment decisions."
Keywords: 650; Wavelets; Interest rates; Stock returns; Industry; Haar á trous wavelet